Exosomal proteins: new targets for early diagnosis and treatment of cancer - Shen, Haibin; Liu, Meijin; Yang, Wentai; Xiao, Dewang; Peng, Zongbo; Rao, Dingyu; Huang, Defa (Frontiers in Immunology, 2025)
Exosomes are nanoscale, double-membraned vesicles released by a variety of living cells. A wide variety of cargoes, including proteins, DNA and RNA, are transported by exosomes to target cells, thereby transmitting biological signals. In addition to being an essential component of the exosomal cargo, exosomal proteins are a reflection of the physiological state of the originating cell, and play an essential part in intercellular communication in numerous diseases, including cancer. The present review provides a summary of the novel uses of exosomal proteins in cancer diagnosis and prognosis, and highlights the distinct qualities that exosomal proteins possess, when compared with typical serological measurements.